Give or take [videorecording (DVD)] - Riccio, Paul; Effros, Jamie; Butz, Norbert Leo; Effros, Jamie; Oteri, Cheri; Tucker, Joanne, 1982- (Breaking Glass Pictures, 2022)
A man's estranged father unexpectedly dies, so he goes home to Cape Cod and prepares the house for sale while sharing it with his father's temperamental live-in boyfriend. Grieving, they circle each other, butt heads, and negotiate how to remember the different man they both loved, and the significance of what he left behind.